2017
DOI: 10.1200/jco.2017.35.8_suppl.18
|View full text |Cite
|
Sign up to set email alerts
|

Comparing patients with breast and prostate cancer in terms of their mental health comorbidities as predictors of cost and utilization.

Abstract: 18 Background: We compared the role played by mental health comorbidities in the health care cost and utilization of non-elderly patients with breast and prostate cancer. Methods: The Military Health System affords its beneficiaries equal access to medical care. We performed a cross-sectional analysis using administrative data of all 9.5 million beneficiaries, ages 18-64, with direct care and a primary diagnosis of either invasive breast or prostate cancer during FY2007–FY2014. We used regression models to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Meta-regression between the gap in screeing rates between the general population and subjects with mental illness, and the screening rates in the general population. (116) no data available Aggarwal, 2010 (117) no data available Andreassen, 2019 (118) no data available Baughman, 2016 (119) no data available Bires, 2016 (120) no data available Burke, 2017 (121) no data available Caruso, 2012 (122) no data available…”
mentioning
confidence: 99%
“…Meta-regression between the gap in screeing rates between the general population and subjects with mental illness, and the screening rates in the general population. (116) no data available Aggarwal, 2010 (117) no data available Andreassen, 2019 (118) no data available Baughman, 2016 (119) no data available Bires, 2016 (120) no data available Burke, 2017 (121) no data available Caruso, 2012 (122) no data available…”
mentioning
confidence: 99%
“…To our knowledge, this is the first study to observe that depressive symptoms documented in the medical record are associated with longer hospital LOS in patients with advanced cancer. Prior studies in the general medicine literature and among patients with cardiovascular and pulmonary disease have shown associations between psychological distress and increased use of health care services , yet relatively few studies from the oncology setting have linked depression with increased health care utilization . Explanations for the association between depressive symptoms and prolonged hospital LOS include the potential effects of patients’ psychological symptoms on their treatment adherence, health‐seeking behaviors, and physical symptoms such as pain or fatigue .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, research has demonstrated that depressive symptoms are associated with greater health care utilization in patients with cancer, particularly longer hospital length of stay (LOS) . However, although therapies are available to help address depressive symptoms in patients with cancer, prior studies have not investigated the potential impact of such therapies on the use of health care services.…”
Section: Introductionmentioning
confidence: 99%